How to do a thoracoscopic‐assisted oesophagectomy with oesophagogastric anastomosis using a circular stapler. Issue 7 (26th July 2021) - Schofield, Adam; McQuillan, Patrick; Kanhere, Harsh; Prasad, Shalvin
Abstract : Thoracoscopic mobilization of the oesophagus during oesophagectomy has many advantages over the traditional open approach including less blood loss, reduced pulmonary complications and shorter hospital stay. Minimally invasive intrathoracic oesophagogastric anastomosis can be technically challenging, with several different techniques described in the literature. Here, we describe a nuanced technique to perform an intracorporeal anastomosis using a circular stapler.